1986
DOI: 10.1007/bf00266208
|View full text |Cite
|
Sign up to set email alerts
|

Factors predisposing to patellar chondropathy and patellar apicitis in athletes

Abstract: Factors predisposing to patellar chondropathy (the PC group) and inferior patellar apicitis (jumper's knee - the PA group) were sought by means of a questionnaire, detailed quantitative physical measurements and radiological examination in male athletes. There were 20 athletes in the two groups who had typical symptoms and signs of each disorder. A group of 20 high-level athletes without knee symptoms served as a control group. The factors found in the PC group which differed significantly from those in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0
6

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 25 publications
5
60
0
6
Order By: Relevance
“…Patella alta has been reported to be associated with patella subluxation, episodic dislocation, and patellofemoral joint instability [18,31]. Patellofemoral malalignment associated with patella alta is believed to cause excessive wear of the cartilage, contributing to the development of patellofemoral pain and arthritis [13,15,27]. Biomechanical studies have shown that patella alta can result in decreased patellofemoral joint contact area and elevated contact stresses [26,30,32].…”
Section: Introductionmentioning
confidence: 99%
“…Patella alta has been reported to be associated with patella subluxation, episodic dislocation, and patellofemoral joint instability [18,31]. Patellofemoral malalignment associated with patella alta is believed to cause excessive wear of the cartilage, contributing to the development of patellofemoral pain and arthritis [13,15,27]. Biomechanical studies have shown that patella alta can result in decreased patellofemoral joint contact area and elevated contact stresses [26,30,32].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, patella alta has been biomechanically and clinically linked to increased incidence of AKP [28][29][30][31] and present in 30 % of patients with PF disorders and in 0 % of controls [15,22]. There are also reports of a group of patients with 'potential patellar instability', in whom trochlear dysplasia and/or patella alta are present and causing AKP but with no history of patellar dislocation [15].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Several factors have been associated with anterior knee pain, including patella alta, [3][4][5] but the precise mechanism by which this leads to anterior knee pain remains poorly understood.…”
mentioning
confidence: 99%